The Effect of Electrolytes on the Kinetics of the Hydrogen Evolution Reaction - Goitom K. Gebremariam; Aleksandar Z. Jovanović; Igor A. Pašti (Hydrogen, 2023)
Amid global energy challenges, the hydrogen evolution reaction (HER) is gaining traction for green hydrogen production. While catalyst research is ongoing, recognizing electrolyte effects remains crucial for sustainable hydrogen production via renewable-powered water electrolysis. This review delves into the intricate effects of electrolytes on the kinetics of the HER. It examines key factors including the pH, cations, anions, impurities, and electrolyte concentration. This review discusses the notion that the electrolyte pH alters catalyst–electrolyte interactions and proton concentrations, thereby influencing factors such as the hydrogen binding energy, water adsorption, and overall reaction kinetics. Moreover, this review provides a briefing on the notion that electrolyte cations such as Li+ can impact the HER positively or negatively, offering opportunities for improvement based on the metal substrate. Interestingly, there is a potential that the HER can be tuned using Li+ ions to modify the M–H bond energy, demonstrating a flexibility beyond the pH levels and counter-ions. The varied adsorption energies of metal cations on metal electrodes are also found to influence the HER kinetics. The effects of electrolyte anions and impurities are also discussed, emphasizing both the positive and negative impacts on HER kinetics. Moreover, it is pointed out that the electrolyte-engineering approach enhances the HER kinetics without permanent catalyst surface modifications. This review underscores the importance of the electrolyte composition, highlighting both the challenges and potential solutions in advancing HER research for sustainable energy production.